Evolution of the concept of device moving from internet of things to artificial intelligence of things - Paolone, Gaetanino; Pilotti, Francesco; Piazza, Andrea (International Journal of Electrical and Computer Engineering (IJECE), 2024)
The internet of things (IoT) refers to a network of physical devices that are embedded with sensors, software, and network connectivity, allowing them to collect and share data. The devices are the core of any IoT ecosystem. Browsing the extant literature, it emerges that the meaning of the term device depends on the reference context. It follows that, it is an important topic to investigate the reasons behind such a degree of indeterminacy. This paper elaborates on the evolution of the concept of device moving from IoT to artificial intelligence of things (AIoT). The finding that comes from this study is that this evolution is a direct consequence of the evolution of the IoT computing paradigms.